EVALUATION OF TWO GENOTYPES OF GUINEA PIGS (Cavia porcellus) FED WITH CONCENTRATED AND EXCLUSION OF FORAGE - Camino M., Javier (2014)
The aim of the study was to evaluate the productive performance and percent of fat in the carcass of two guinea pig(Cavia porcellus) genotypes fed for nine weeks with two types of diets. A Randomized Complete Design with 2x2 factorial arrangements was used: two genotypes (Cieneguilla-UNALM and Peru-INIA) and two diets (diet 1: concentrate supplement, forage and water, and diet 2: concentrate supplement with vitamin C and water). The final body weight, daily weight gain, dry matter intake, feed conversion, carcass weight and yield, and fat and moisture percentage of the carcasses were evaluated. The final body weight, body weight gain, feed conversion and carcass weight at 12 weeks of age in Cieneguilla animals was 1266 g, 15.6 g/day, 3.14 and 878 g respectively whereas in Peru animals was 1154 g, 13.6 g/day, 3.54 and 765 g respectively (p<0.05). The genotype did not affect dry mater intake, carcass yield, or fat and moisture percentage. Moreover, neither the type of diet nor the interaction genotype x diet were significant factors affecting the parameters under evaluation.